Areas of Use of Euphemisms in Modern English Using the Example of Women’s and Men’s Glossy Magazines (Eurasian Scientific Herald, 2023)
This work is devoted to the analysis of euphemisms in English and Russian languages. The type of vocabulary we are studying is of great interest for study. Euphemisms are an active tool of language; they directly depend on the communicative situation and the position of the addresser and addressee in society, on the characteristics of their culture and the mentality of the country in which they live.